Instability in the environment and children’s in-school self-regulatory behaviors - Smith, Karen E.; Dimitroff, Stephanie J.; Faig, Kelly E.; Silver, Emily M.; Norman, Greg J. (Frontiers in Psychology, 2025)
IntroductionExperiences of chronic and/or extreme stress early in childhood are associated with altered self-regulatory behaviors. However, there is a range of variability in children’s behavioral outcomes after experiences of stress. Understanding what contributes to this variability in children’s responses to stress can aid in the development of more effective programs aimed at supporting children’s self-regulatory processes. The current study examined relationships between indices of environmental stability and changes in children’s self-regulatory behaviors.MethodsRatings of children’s self-regulatory behavior were collected in collaboration with a school program once a month over the course of the academic year. Measures of environmental stability were collected for each child.ResultsChildren demonstrated increases in self-regulatory behaviors over the course of the study. Additionally, children in home environments characterized by high levels of environmental instability demonstrated greater positive behavior change during the program.DiscussionThis study suggests that there are important individual differences in children’s patterns of self-regulatory behavior changes, and points to complex interactions between children’s home environment, implementation of a more positive and stable environment, and changes in behavior.